Aplikasi Seduhan Zingiber Officinale (Jahe) Terhadap Defisit Nutrisi Pada Ibu Hamil Trimester I Di Wilayah Kerja Puskesmas Cikalong kulon Kabupaten Cianjur - Siti Nuraini; Dhinny Novryanthi; Eva Martini (Fakultas Kesehatan Universitas Muhammadiyah Sukabumi, 2021)
During pregnancy, mothers experience physical, social and emotional changes in the family environment. Any pregnancy can also develop into problems or complications at any time. That's why pregnant women need monitoring during pregnancy. Hormonal changes in women occur during pregnancy, namely an increase in the hormones progesterone and estrogen, resulting in placental HCG or (Human Chorionic Gonadotropine). This can cause complaints that will be experienced by pregnant women, one of which is emesis gravidarum or nausea and vomiting that occurs in pregnancy can cause nutritional disorders, dehydration, weakness, weight loss, and electrolyte imbalances in the body which can have a negative impact on development. such as abortion, low birth weight babies, premature birth, malformations of the fetus, stunted fetal growth. The purpose of this study was to understand and apply the infusion of zingiber officinale (ginger) to nutritional deficits in first trimester pregnant women. Data collection methods were interviews, observation, and lateral/documentation studies. Interventions were carried out to overcome nausea and vomiting by steeping ginger (zingiber officinale) to meet the nutritional needs of pregnant women. It can be concluded that the administration of steeping ginger (zingiber officinale) can reduce nausea and vomiting in pregnant women in the first trimester. The results of this study are expected to be a reference for future researchers.